2023
DOI: 10.3389/fneur.2023.1096153
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and predicting the risk of death in stroke patients using machine learning

Abstract: BackgroundStroke is an acute disorder and dysfunction of the focal neurological system that has long been recognized as one of the leading causes of death and severe disability in most regions globally. This study aimed to supplement and exploit multiple comorbidities, laboratory tests and demographic factors to more accurately predict death related to stroke, and furthermore, to make inferences about the heterogeneity of treatment in stroke patients to guide better treatment planning.MethodsWe extracted data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…As seen in prior literature, there is a well-established correlation between higher age and increased stroke mortality [ 26 , 58 , 59 ]. In this study, the mean age was 54 ± 13.5 years, which could be considered comparatively lower when assessed on regional and global scales [ 7 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As seen in prior literature, there is a well-established correlation between higher age and increased stroke mortality [ 26 , 58 , 59 ]. In this study, the mean age was 54 ± 13.5 years, which could be considered comparatively lower when assessed on regional and global scales [ 7 ].…”
Section: Discussionmentioning
confidence: 82%
“…SHAP analysis corroborated that BMI significantly contributes to the model's predictions. In general, obesity stands as a notable risk factor for stroke development and poor prognosis [ 21 , 26 ]. However, a considerable body of prior research has shown a counterintuitive correlation between BMI and stroke outcomes, reflecting a negative association [ 21 , [78] , [79] , [80] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHAP analysis reaffirmed the significant influence of BMI on the model’s classification performance. Typically, obesity is well-recognized as a leading risk factor for stroke and is linked with unfavorable prognoses [ 41 , 42 ]. A study conducted in Qatar in 2009 similarly identified obesity as one of the major risks associated with PCS, finding that patients with a BMI > 30 faced a heightened risk of PCS compared to those with lower BMIs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to the fact that a patient cannot simultaneously receive both treatments, and confounding variables are prevalent in observational studies ( 15 ). Benefitting from advances in machine learning (ML) and statistical theories, we can use balanced representation-based ( 16 ), tree-based ( 17 ), and conditional average treatment effect (CATE)-based ( 18 , 19 ) methods to counterfactually infer patients’ individual treatment effect (ITE) directly from observational data and thus attempt identify the relatively optimal treatment choice for specific individuals. With the development of deep learning (DL) and representation learning, novel techniques enable combining DL with survival models and learning balanced representations directly from the data to reason about unbiased counterfactual survival outcomes ( 20 ).…”
Section: Introductionmentioning
confidence: 99%